INTERNALIZATION OF VALUES IN FORMING STUDENT CHARACTERS THROUGH EXTRACURRICULAR ACTIVITIES OF TAHFIDZUL QUR'AN AT PRIVATE SD GENERATION OF NATION MEDAN LABUHAN - Hafsah Hafsah; Salmuddin Salmuddin; Nurhasanah Nurhasanah (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
This study aims to determine (1) how the spiritual values in the extracurricular activities of Tahfidzul Qur'an in SD Swasta Generasi Bangsa(3) What are the obstacles in instilling spiritual values through extracurricular activities on Tahfidzul Qur'an to shape the character of students at SD Swasta Generasi Bangsa. This research is a type of qualitative research with a descriptive approach. In the process of collecting data, researchers used observation, interview and documentation methods. The results show that (1) the spiritual value of the extracurricular activities of Tahfidzul Qur'an is divided into 3 values, namely the value of faith/faith obtained through reciting prayers and Asma'ul Husna, muraja'ah surah and its verses, and always loving the Alqur'an. reading it, the value of piety / worship lies in reading the Alqur'an which is included in worship and other worship practices such as prayer both sunnah and compulsory, moral value lies in the authority of a teacher and the advice given so that students always say good, polite, respect people others and are afraid to commit immorality. (2) The process of cultivating spiritual values is carried out through extracurricular activities of Tahfidzul Qur'an with habituation, the method used in learning is a combined method, the learning strategy emphasizes the role of the supervisor, daily evaluation by checking memorization, monthly evaluation with verse connecting games, and evaluation. semester with the Tahfidz exam. From the internalization of spiritual values in the extracurricular activities of Tahfidzul Qur'an, it forms character in students, namely religious, disciplined, and friendly / communicative. (3) Obstacles in instilling spiritual values in shaping student character through extracurricular activities of Tahfidzul Qur'an are student awareness, very limited learning time, and there is no good collaboration between schools and parents. The solution to these obstacles is the reward and punishment method, time efficient learning of Tahfidzul Qur'an, as well as parents who control their children at home and accompanied by a connecting book